1990
DOI: 10.1128/jcm.28.7.1493-1496.1990
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative immunoassay of Treponema denticola serovar C in adult periodontitis

Abstract: Murine monoclonal antibodies specific for Treponema denticola serovar C were produced and characterized in this study. An immunoassay was then developed by using these monoclonal antibodies, and the T. denticola serovar C antigen content of subgingival plaque was quantitated for samples taken from patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…77 dentteota, a spirochete that can be cultured in vitro from subgingival plaques, was originally grouped into at least 3 serovars on the basis of the sero-logical agglutination test and fluorescent immunoassay with absorbed antisera (4). The serovars A, B and C are denoted as ATCC 35405, ATCC 33521 and ATCC 33520 (or ATCC 35404), respectively (21,23,34). Our study showed that the ATCC 33520 and 35404 strains carried the common P3, P4, P5, P6, P9, PIO, PI 1 and P14 polypeptide antigens.…”
Section: Acknowledgementsmentioning
confidence: 71%
See 3 more Smart Citations
“…77 dentteota, a spirochete that can be cultured in vitro from subgingival plaques, was originally grouped into at least 3 serovars on the basis of the sero-logical agglutination test and fluorescent immunoassay with absorbed antisera (4). The serovars A, B and C are denoted as ATCC 35405, ATCC 33521 and ATCC 33520 (or ATCC 35404), respectively (21,23,34). Our study showed that the ATCC 33520 and 35404 strains carried the common P3, P4, P5, P6, P9, PIO, PI 1 and P14 polypeptide antigens.…”
Section: Acknowledgementsmentioning
confidence: 71%
“…Discontinuous SDS-PAGE was conducted on the basis of the method of Laemmli as reported previously (II). A mixture of each bacterial suspension (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) fig of protein per lane) and solubilization buffer was heated at 100 C for 5 min and applied to 1-or 2-mmthick SDS-10% acrylamide gels. A total of 13 polypeptides were selected on the basis of individual quantity, clear separation from neighboring protein bands and exclusion of the antigens with apparently similar molecular sizes.…”
Section: Sds-page and Polyclonai Antisera Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported that a strain-specific 53,000-(53-kDa) antigen of T denticola American Type Culture Collection (ATCC) strain is located on the surface of the outer envelopes and that this major polypeptide might share with hexagonally arranged polygonal structure each possessing three pores in the outer envelopes (18,19). Some antigenic proteins were also found in human oral spirochetes and were utilized as probes or indicators to examine their associations with periodontal diseases (9,13,14,21). These types of antigenic proteins may be located in their axial flagella as well as on the outer envelopes.…”
Section: Strainsmentioning
confidence: 99%